Ng Wei Sheng named recipient of Heitech Excellence Award - Siti Nurfarmy, Ibrahim (2022)
PAYA BESAR, 6 November 2022 – “Do not day-dreaming and live in the present moment. Do not get stuck in the past and fixated on the future”, such are the words held dearly by Ng Wei Sheng, 24 graduate of Universiti Malaysia Pahang (UMP), who received the Heitech Excellence Award at the recent UMP 17th Convocation Ceremony.